Host genetic factors associated with hepatocellular carcinoma in patients with hepatitis C virus infection: a systematic review - Walker, Alex J.; Peacock, Christian J.; Pedergnana, Vincent; Irving, William L. (Wiley, 2018)
Hepatitis C virus (HCV)-infected patients are at risk of developing hepatocellular carcinoma (HCC). Individuals at heightened riskcould be targeted by intensive follow-up surveillance. We have conducted a systematic review of the literature to identify host genetic predisposition to HCC in HCV-infected patients. A comprehensive search of Medline and Embase databases was performed and the strength of evidence of associations for each gene on development of HCC was evaluated. We identified 166 relevant studies, relating to 137 different genes, or combinations thereof. 17 genes were classified as having “good” evidence of an association, a significant association was observed for 37 genes but this finding had not yet been replicated, 56 genes had mixed or limited evidence of an association, and 27 genes showed no association. IFNL3/4, TNF-α and PNPLA3 genes had the most evidence of an association. There was, however, considerable heterogeneity in study design and data quality. In conclusion, we identified a number of genes with evidence of association with HCC, but also a need for more standardised approaches to address this clinically critical question. It is important to consider the underlying mechanism of these relationships and which are confounded by the presence of other HCC risk factors and response to therapy. We also identified many genes where the evidence of association is contradictory or requires replication, as well as a number where associations have been studied but no evidence found. These findings should help to direct future studies on host genetic predisposition to HCC in patients with HCV infection.